FORMATION OF ENVIRONMENTAL COMPETENCE OF HEARING-IMPAIRED STUDENTS IN EXTRACURRICULAR ACTIVITIES IN SCIENCE - Haydarov Islamjan (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the content of the formation of environmental competence of students with hearing impairment in extracurricular activities in science. In science extracurricular activities, various activities related to the study and conservation of nature, growing plants, and caring for animals are analyzed.